Research priorities relating to the debate on assisted dying: what do we still need to know? Results of a modified Delphi technique - Rodgers, Mark; Booth, Alison; Norman, Gill; Sowden, Amanda (BMJ open, 2016)
ObjectiveTo identify the main areas of uncertainty and subsequent research priorities to inform the ongoing debate around assisted dying.DesignTwo-round electronic modified Delphi consultation with experts and interested bodies.Setting and participants110 groups and individuals interested in the subject of end-of-life care and/or assisted dying were approached to participate. Respondents included health and social care professionals, researchers, campaigners, patients and carers predominantly based in the UK. In the first round, the respondents were asked to propose high-priority research questions related to the topic of assisted dying. The collected research questions were then deduplicated and presented to all respondents in a second round in which they could rate each question in terms of importance.Results24% and 26% of participants responded to the first and second rounds, respectively. Respondents suggested 85 unique research questions in the first round. These were grouped by theme and rated in terms of importance in the second round. Emergent themes were as follows: palliative care/symptom control; patient characteristics, experiences and decisions; families and carers; society and the general public; arguments for and against assisted dying; international experiences/analysis of existing national data; suicide; mental health, psychological and psychosocial considerations; comorbidities; the role of clinicians; environment and external influences; broader topics incorporating assisted dying; and moral, ethical and legal issues. 10 of the 85 proposed questions were rated as being important (≥7/10) by at least 50% of respondents.ConclusionsResearch questions with the highest levels of consensus were predominantly concerned with understanding how and why people make end-of-life decisions, and which factors influence those decisions. Dissemination of these findings alongside a focused examination of the existing literature may be the most effective way to add evidence to the ongoing debate around assisted dying.